DEGRADASI SENYAWA RHODAMIN B SECARA SONOLISIS DENGAN PENAMBAHAN TiO2 HASIL SINTESA MELALUI PROSES SOL-GEL - Arief, Syukri; -, Safni; Roza, Putri Perdana (Jurnal Riset Kimia, 2007)
ABSTRACTDegradation of rhodamine B had been done by sonolysis method. Optimum temperature sonolysis were found of 41-50 oC. In this condition, rhodamine B 2 mg/L could be degradated around 64.04% during 6 hours sonolysis. Percentage degradation of rhodamine B enhanced by addition of TiO2 in solution. TiO2 was prepared with sol-gel process using titanium isopropoxide (TIP), isopropanol and dietanolamine (DEA) as precursor. It was heated on 500 oC and 700 oC in order to get TiO2-anatase dan TiO2-rutile. Rhodamine B 2 mg/L could be degradated around 68.48 and 90.00 % during 6 hours sonolysis on optimum temperature with addition of 0.1 g  TiO2-rutile and TiO2-anatase, respectively. Keyword: rhodamine B, sonolysis, sol-gel